A Tale of Three Cities - Eisman, Michael Max 1936- (1978)
A study of the urban development of Jerusalem, Athens, and Rome, the three great ancient cities which are the fountain-heads of western civilization. The response that each made to its own urban crisis determined its place in history forever.